ANALISA KESEHATAN KEUANGAN PT. BANK BUKOPIN TBK - Rina Nopianti (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2017)
Bank Bukopin (Persero) Tbk is one of the Indonesian government-owned banks. Bank Bukopin continuously conducts evaluations and improvements, especially in the areas of service, product development, marketing functions and development of office network, in order to realize the vision as a trusted bank in financial services. This is evident from the analysis of financial performance in the period 2014-2016 which shows an increasing trend every year. The purpose of this study are: